2009
DOI: 10.4103/0253-7613.58515
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac-induced biochemical and histopathological changes in white leghorn birds (Gallus domesticus)

Abstract: Objective:Objective: To evaluate diclofenac-induced biochemical and histopathological changes in White Leghorn birds.Materials and Methods:Six-week-old birds were equally divided into three groups of six birds each. Group I served as control and received vehicle orally. The birds of Group II and III were orally administered with a single low (2 mg/kg) and high dose (20 mg/kg) of diclofenac sodium, respectively, and were observed for 7 days. The acute toxicity was assessed by observing the clinical signs and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…For this study we intentionally chose high doses as we wanted to follow the lethal changes following exposure to diclofenac. As expected, following the administration of 10 mg/kg diclofenac as a single dose, mortality rate of 33% was recorded within 48 h, which were similar to previous mortalities of 40% evident in white leghorn after 12 days of exposure to 10 mg/kg of diclofenac ( Jain et al, 2009 ; Reddy et al, 2006 ) and the LD 50 of 10 mg/kg reported after a single dose exposure in layer hens, and confirmed in Ross broilers of 4 weeks age ( Naidoo et al, 2007 ; Locke, 2020 ). Furthermore, histopathology changes observed in the two domestic chickens that died following diclofenac exposure, were similar to those reported in the Leghorn and Gyps species ( Oaks et al, 2004 ; Meteyer et al, 2005 ; Swan et al, 2006b ; Jain et al, 2009 ; Naidoo et al, 2007 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For this study we intentionally chose high doses as we wanted to follow the lethal changes following exposure to diclofenac. As expected, following the administration of 10 mg/kg diclofenac as a single dose, mortality rate of 33% was recorded within 48 h, which were similar to previous mortalities of 40% evident in white leghorn after 12 days of exposure to 10 mg/kg of diclofenac ( Jain et al, 2009 ; Reddy et al, 2006 ) and the LD 50 of 10 mg/kg reported after a single dose exposure in layer hens, and confirmed in Ross broilers of 4 weeks age ( Naidoo et al, 2007 ; Locke, 2020 ). Furthermore, histopathology changes observed in the two domestic chickens that died following diclofenac exposure, were similar to those reported in the Leghorn and Gyps species ( Oaks et al, 2004 ; Meteyer et al, 2005 ; Swan et al, 2006b ; Jain et al, 2009 ; Naidoo et al, 2007 ).…”
Section: Discussionsupporting
confidence: 87%
“…Diclofenac toxicity in the vultures and chickens is characterized by major increases in plasma uric acid and subsequent gout (Oaks et al, 2004;Meteyer et al, 2005;Reddy et al, 2006;Naidoo et al, 2007;Jain et al, 2009). From mammalian physiology it is known that diclofenac has the ability to inhibit both the functions of the OAT channel, reduce blood supply to the kidney and alter glomerulus filtration (Khamdang et al, 2002;Anzai, Kanai & Endou, 2006;Katzung, Masters & Trevor, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…NSAIDs bind strongly to plasma protein and are metabolised mainly in the liver, usually to inactive compounds (Lees et al 2004 ). Plasma, liver and kidney can all be used to monitor NSAID exposure and can also be used for effects assessment, since diclofenac-treated vultures have shown an increase in plasmatic uric acid, alanine transferase and glutamic pyruvate transaminase, and histopathological changes in kidneys and liver (Swan et al 2006 ; Jain et al 2009 ); visceral gout has also been a key indicator of exposure (Cuthbert et al 2015 ). Data regarding the safety of other NSAIDs and risks to other species is currently limited (Taggart et al 2009 ; García-Fernández 2014 ; Sharma et al 2014 ); and further monitoring of NSAIDs concentrations in raptor populations and evaluation of potential effects therefore remains a priority.…”
Section: Monitoring Other Contaminants Of Current and Emerging Concermentioning
confidence: 99%